2022
DOI: 10.17269/s41997-022-00693-x
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine hesitancy among young adults in Canada

Abstract: Objectives Vaccine hesitancy is a multifaceted decision process that encompasses various factors for which an individual may choose to get vaccinated or not. We aimed to identify the relationship between COVID-19 conspiracy theories, general attitudes towards vaccines, current COVID-19 vaccine factors, and COVID-19 vaccine hesitancy. Methods The present research is a multi-province cross-sectional study design. Survey data were collected in May and June 2021 ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In addition, their decisions were influenced by information overload, difficulty separating misinformation from scientific evidence, and difficulty believing scientific evidence. Another survey reported that vaccine-hesitant Canadians aged 18-40 years were influenced by conspiracy theories and a distrust of governments [ 20 ]. Furthermore, protests against public health regulations indicate high levels of distrust of COVID-19 information [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, their decisions were influenced by information overload, difficulty separating misinformation from scientific evidence, and difficulty believing scientific evidence. Another survey reported that vaccine-hesitant Canadians aged 18-40 years were influenced by conspiracy theories and a distrust of governments [ 20 ]. Furthermore, protests against public health regulations indicate high levels of distrust of COVID-19 information [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…None of the 45 studies from 7 countries were focused on decision-making needs during pandemics [ 10 ]. A recent cross-sectional study of 4905 Canadians aged 18-40 years reported that factors associated with vaccine hesitancy are negative attitudes toward vaccines in general; COVID-19 conspiracy theory beliefs; distrust of the government; and a low income, low education, or unemployment [ 20 ]. Canada was no exception, as little was known about its health-related decision-making experience during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…As the success of public health policy often depends upon the cooperation of the public, it is important that the public perception of scientific advice, in this case specifically mathematical modelling, is understood. Much of the research into public opinions throughout the COVID-19 pandemic has related to vaccine hesitancy [7][8][9] or adherence to public health and social measures [10][11][12][13]. Although Marshall et al [14] interviewed members of the public regarding Test, Trace and Isolate policies with a view to improving assumptions underpinning mathematical modelling, respondents were not explicitly asked about their perceptions of modelling.…”
Section: Introductionmentioning
confidence: 99%